Дорожні цементобетони на основі модифікованих добавок нової генерації - Собко, Ю. М.; Шевчук, Г. Я.; Топилко, Н. І.; Новицький, Ю. Л.; Sobko, Y.; Shevchuk, H.; Topylko, N.; Novytskjy, Y. (Видавництво Львівської політехніки, 2018)
Розроблено склади модифікованих бетонних сумішей і цементобетонів із заданими експлуатаційними параметрами. В процесі проведення експерименту цементобетони отримували із бетонних сумішей різних складів з модифікуючими добавками нової генерації, які містять суперпластифікатор на основі полікарбоксилатів та повітрезахоплюючу добавку. Суперпластифікатор вводили до бетонної суміші з водою замішування в кількості 0,6; 0,8 і 1,0 % маси цементу, а добавку-аерант – в кількості 0,1 % маси цементу до усіх складів бетонів. Досліджено вплив модифікуючих добавок на властивості дорожніх цементобетонів. Показано ефективність їх використання в дорожніх покриттях, що забезпечує покращені технологічні параметри, підвищену міцність та довговічність. Повітрезахоплююча добавка-аерант в комплексі із суперпластифікатором дає змогу посилити пластифікацію бетонної суміші, а також підвищити морозостійкість та водонепроникність. Визначено техніко-економічну ефективність застосування дорожніх цементобетонів на основі модифікуючих добавок нової генерації та встановлено, що конструкція із цементобетонного покриття дешевша в 1,6 разу ніж конструкція дорожнього одягу із асфальтобетону за вартістю будівельномонтажних робіт.

The modified concrete mixes design and cement concrete with the given operational parameters was developed. During the experiment, cement concrete was obtained from concrete mixtures of various compositions with modifying additives of a new generation containing a superplasticizer based on polycarboxylates and an air-absorbent additive. Superplasticizer was injected into a concrete mix with water in a quantity of 0,6; 0,8 and 1,0 % of the mass of cement, and the additive-aeration – in the amount of 0,1 % of the mass of cement in all the components of concrete. The influence of modifying additives on the properties of road cement concrete has been investigated. The effectiveness of their use in road surfaces is shown, which provides improved technological parameters, increased strength and durability. Air-absorbent additive-airant, in combination with a superplasticizer, allows to enhance the plasticization of the concrete mixture, as well as increase the frost resistance and waterproofness. The introduction of a modifying additive from 0,6 to 1,0 % ensures an increase in the strength of concrete in the early hardening period (2 days) from 8,7 to 11,0 MPa. After a month of hardening the strength of such concrete is 39,2 – 39,9 MPa, which corresponds to the class of concrete B30. The use of a modifying additive during the preparation of a concrete mix allows the design of concrete with a water-cement ratio, which will reduce the open porosity of the concrete, increase its density, and thereby prevent the formation of highlands on the surface of concrete. When introducing a modifying additive, porosity is reduced by 1,4-2 times, which correlates with the results on the strength of concrete. The techno-economic efficiency of the use of road cement concrete on the basis of new generation modifying additives was determined and the construction of cement-concrete coating was found to be cheaper by 1,6 times the construction of road pavement from asphalt concrete in comparison with the cost of construction and installation work.
Road cement concretes based on modified additives of new generation
Keywords: дорожній цементобетон; модифікуюча добавка; міцність; дорожнє покриття; road cement concrete; modification additive; strength; road pavement; 666.972.16